Comparative evaluation of subgingival irrigation with propolis extract versus chlorhexidine as an adjunct to scaling and root planing for the treatment of chronic periodontitis: A randomized controlled trial - Tejashvi Ashok Seth; Triveni Ashok Kale; Shruti Shankarrao Lendhey; Pallavi Vilas Bhalerao (Wolters Kluwer Medknow Publications, 2022)
Background: This study was carried out to investigate the effectiveness of subgingival irrigation with propolis extract compared to chlorhexidine as an adjunct to mechanical debridement to bring out the restoration of periodontal health in patients with chronic periodontitis. Materials and Methods: Twenty subjects were selected and randomly assigned into two groups of ten subjects each, which received subgingival irrigation with 0.2% chlorhexidine (control group) and propolis extract (test group) after initial scaling and root planing on the 7th day and 15th day as an adjunctive treatment. Plaque index (PI), gingival index (GI), and probing pocket depth (PPD) were assessed at baseline, on the 15th day, and on the 30th day. Microbial analysis for the colony-forming unit (CFU) was done at baseline and on the 30th day. Results: Statistically significant reduction was observed in PI, GI, PPD, and CFU counts from baseline to 30 days in both the groups. On intergroup comparison, the group received irrigation with chlorhexidine showed slightly better results; however, this difference was statistically nonsignificant compared to the group that received irrigation with propolis. Conclusions: It was concluded that propolis extract is as effective as chlorhexidine as a subgingival irrigant in reducing the subgingival plaque formation and microbiota from periodontal pockets.